The Fat Tail : the Power of Political Knowledge in an Uncertain World (with a New Preface). - Bremmer, Ian, 1969- (Oxford University Press, USA, 2010)
As Ian Bremmer and Preston Keat reveal in this innovative book, volatile political events such as the 2008 Georgia-Russia confrontation--and their catastrophic effects on business--happen much more frequently than investors imagine. On the curve that charts both the frequency of these events and the power of their impact, the "tail" of extreme political instability is not reassuringly thin but dangerously fat. Featuring a new Foreword that accounts for the cataclysmic effects of the 2008 financial crisis, The Fat Tail is the first book to both identify the wide range of political ris.